Ultrafast Machining through Heating Laser-Excited Electrons - Guoqi Ren; Huijie Sun; Takumi Koike; Kota Takabayashi; Keiichi Nakagawa; Naohiko Sugita; Yusuke Ito (Ultrafast Science)
Although the precision ablation of transparent hard and brittle materials using ultrashort pulse lasers has been widely investigated, the speed of material removal remains low. In this study, we achieved ultrafast and precise material removal by creating a long-lifetime plasma filament inside the material and sufficiently heating it. A crack-free microhole with a depth of approximately 60 μm and a diameter of approximately 4 μm was generated within 2 μs. The machining speed was 4.3 × 104 times faster than conventional femtosecond laser processing. The dynamics of the plasma filament induced by an ultrashort pulse laser were investigated using the pump-probe method, indicating a slow decay of excited electrons owing to their high density. Through experiments and simulations, we revealed that a microsecond laser pulse can more effectively heat the plasma filament for material removal because of higher energy absorption. Moreover, the timing between filament generation and laser heating plays a critical role in machining due to the relaxation of excited electrons. This work provides an attractive route for advanced precision fabrication in industrial applications, as well as for facilitating the understanding of laser–matter interactions.